Physiological response and phytochemical content of Andrographis paniculata (Burm.) as affected by light and nitrogen - Rosli, Khairul Azree (2013)
Andrographis paniculata (Burm.) Nees or hempedu bumi is a traditional medicinal and aromatic plant with valuable phytochemical and pharmacological potential. Growth, physiological and phytochemical responses to light and nitrogen are useful measurements to determine favorable growing conditions for hempedu bumi. Despite numerous findings on other medicinal and aromatic plants, there are no literatures on how light and nitrogen affect growth, physiology and phytochemical content of hempedu bumi in the humid tropics of Malaysia. The objectives of this study were to determine the effects of shade and nitrogen on growth, physiology and phytochemical content of hempedu bumi. Plants were grown under two shade levels, 0% and 40%, and fertilized with five nitrogen rates, 90, 135, 180, 225 and 270 kg ha-1 in a nested design. Dependent variables were growth components, gas exchange, chlorophyll fluorescence, relative chlorophyll content, chlorophyll pigments and, leaf nutrient content and uptake, and, andrographolide, neoandrographolide and 14- deoxy-11, 12-didehydroandrographolide concentrations and yields. Shaded plants grew taller with greater total leaf area, specific leaf area, leaf area ratio, net assimilation rate and leaf andrographolide yield than sun-grown plants. Sun-grown plants had higher relative chlorophyll content, total chlorophyll, chlorophyll a, chlorophyll b, ratio of chlorophyll a to chlorophyll b and net photosynthesis rate, leaf concentrations of phosphorus, potassium, calcium and magnesium, and neoandrographolide than shaded plants. Fertilizing plants with increasing rate of nitrogen has increased their height, leaf area index, total leaf area, shoot and root dry mass, leaf mass ratio and root shoot ratio, intercellular carbon dioxide concentration and leaf temperature. There was a quadratic relationship between nitrogen rate and total dry mass of plants. Increasing rate of nitrogen has also increased leaf nitrogen and potassium content, and uptake of phosphorus, calcium and magnesium, and neoandrographolide yield. Shade interacted with nitrogen affecting plant height, leaf area index, total leaf area, leaf dry mass, leaf area ratio, and neoandrographolide and 14-deoxy-11, 12-didehydroandrographolide concentrations. Neoandrographolide and 14-deoxy-11, 12-didehydroandrographolide concentrations per extract were higher in sun-grown plants than in shaded plants. Shade and nitrogen did not affect relative growth rate, chlorophyll fluorescence and yield of 14-deoxy-11, 12- didehydroandrographolide. The goal in commercial hempedu bumi cultivation is to produce plants containing high dry mass and phytochemical content. Hempedu bumi could adapt to varying levels of shade and nitrogen by altering its morphology, physiology and biochemistry. Shading at 40% and fertilizing with nitrogen at 225 kg ha-1 can increase the dry mass and phytochemical content of hempedu bumi.